Types of Sex And Development of Gonad Protoginic Rice Grouper (Cromileptes altivelis) After Hormone Stimulation - Abdul Zahri; Melissa Justin Renjaan; Farida Farida (Jurnal Perikanan dan Kelautan, 2020)
This study aims to analyze the effect of estradiol (E2) and methyltestosterone (MT) combined with hCG on the composition of sex and the gonad development of protogynous humpback grouper (Cromileptes altivelis). The fish experiment 13±1,5g of body weight in the nursery phase. Treatment with a estradiol solution of 3 mg mL–1+ hCG 20 IU mL–1(CE), MT 3mg mL–1+ hCG 20 IU mL–1(CM), estradiol 3 mg mL–1 (E), MT 3 mg mL–1 (M) and 9 mg mL–1 NaCl to control (K). Hormone with dose 1 mL kg–1 was injected on dorsal fin base, with frequency of six times and periode of two weeks. The fish are kept in a 500 liters fiberglass container with a calm water system for 11 months. Fish were fed pellets with protein content of 46% twice daily. The study used a completely randomized design with one treatment factor, the hormone and its combination. Giving hormones with combination, i.e. treatmenth CE and CM was effective to increase the percentage of gonad development with GSI value 0.4161±0.0978% and 0.4161±0.1055%, whilw HSI on CE 0.6456±0.0419% and CM 0.5797±0.1069%  The gonadal histologic observation showed transition pattern and sex change from female to male at treatment M and CM. The MT hormone is able to stimulate masculinization and its performance is more effective when combined with hCG, 90% from sample population. The development of female gonads in the phases of oogonia and male of masculinization result in the phase of spermatogonia.